Gradual Strengthening Of Existing Masonry Houses With Ferrocement Bandaging In Indonesia For Educating The Common People To Be Self-Reliant And Self-Supporting - Ismail, Febrin Anas; Boen, Teddy; Thamrin, Rendy (Jurnal Bangunan, Konstruksi & Desain, 2024)
There are approximately 85 million people’s houses scattered all over Indonesia and almost all are in strong earthquake areas (Boen, 2016). Every time there is an earthquake, people’s houses are damaged or collapse. Therefore, it is urgent that those houses be strengthened to make them earthquake resistant. This paper discusses a gradual strengthening of existing houses using ferrocement bandaging. The gradual strengthening is introduced due to limited funding of the people. It also serves as an educational tool to educate people to be self-reliant and self-sufficient in building their earthquake resistant houses. The first time, maybe the sleeping room shall be strengthened so that if there is an earthquake during night-time, people will be safe and if there is an earthquake during daytime, people can immediately run to that particular room. A global analysis is made of a sample house shaken by Palu, Central Sulawesi earthquake 2018 (Prof. Dr. Ir. Masyhur Irsyam, M.S.E. and Andhika Sahadewa, S.T., M.S.E., Ph.D., 2018) and by West Sumatra earthquake 2009 (Rusnardi, 2009), with one room strengthened to show that the strengthened room can survive the earthquakes. Then the analysis is continued gradually to the other rooms until the masonry house is fully strengthened by ferrocement bandaging.